Clinical implementation of value based healthcare: Impact on outcomes for lung cancer patients. (December 2021) - Demedts, Ingel; Himpe, Ulrike; Bossuyt, Jelle; Anthoons, Geert; Bode, Hannelore; Bouckaert, Bernard; Carron, Kris; Dobbelaere, Stephanie; Mariën, Heidi; Van Haecke, Peter; Verbeke, Wim
Highlights: Implementing patient reported outcomes in clinical care for lung cancer is feasible. Digital follow up is beneficial for lung cancer patients. Treating lung cancer patients in a digital care pathway leads to a longer survival. It results in less emergency department visits and shorter length of stay at the day clinic. Abstract: Value based Healthcare (VBHC) focuses on patient centered outcomes, by incorporating Patient Reported Outcome Measures (PROMS). Expectations on the benefits of VBHC are high, but few data are available that validate its routine use. We wanted to investigate if VBHC is feasible and beneficial for lung cancer patients in clinical practice. Method: We developed a digital transmural care pathway for lung cancer patients. During systemic therapy, patients digitally reported side effects weekly. Every six weeks, quality of life was reported trough EORTC questionnaires. Case-mix variables, treatment approaches and outcome indicators were systematically collected. We evaluated the compliance of the patients with the digitally reporting system and the impact of the care pathway on patient centered outcomes such as emergency department (ED) visits, time spent on the oncology day clinic, survival and quality of death. Results: 221 lung cancer patients were included in the care pathway. 3091 weekly questionnaires were digitally collected. Compliance with the weekly digital follow-up was 92%: 2835 of 3091 questionnaires were completed. Patients in the care pathway had significantly less ED visits (3.5% vs 4.8%, p 0.04) and a shorter length of stay at the day clinic (2.5 h vs 4.1 h, p < 0, 05) compared to routine clinical care. In stage IV lung cancer patients, overall survival was significantly higher in the care pathway (447 days (95% CI 379–663)) compared to routine care (286 days (95% CI 191–400)) (p = 0, 025). Conclusion: Implementation of value based healthcare is feasible and beneficial in daily clinical care for lung cancer patients.